Circulating vascular endothelial growth factor receptor-3, a pro-lymphangiogenic and pro-angiogenic mediator, is decreased in pre-eclampsia - Palei, Ana C.; Kaihara, Julyane N. S. [UNESP]; Cavalli, Ricardo C.; Sandrim, Valeria C. [UNESP] (Wiley, 2025)
Objective: To compare circulating levels of vascular endothelial growth factor receptor 3 (VEGFR-3) in women with pregnancy-induced hypertension (PIH) and in non-pregnant (NP) and healthy pregnant (HP) women. Methods: We conducted a case–control study including PIH (n = 135), HP (n = 68), and NP (n = 49) women from southeastern Brazil. PIH were diagnosed according to international guidelines, and defined as gestational hypertension (GH, n = 61) or pre-eclampsia (n = 74). VEGFR-3 was measured in plasma using ELISA. Results: Plasma VEGFR-3 was increased in HP (1207 pg/mL) compared with NP (133 pg/mL) women; however, PIH (729 pg/mL) patients exhibited lower levels than HP women (both p < 0.05). In addition, plasma VEGFR-3 was decreased in pre-eclampsia compared with GH (537 versus 980 pg/mL; p < 0.05). When pre-eclampsia was classified according to different clinical presentations, plasma VEGFR-3 was further decreased in the cases identified as pre-eclampsia with severe features, preterm pre-eclampsia, and pre-eclampsia accompanied by small for gestational age (all p < 0.05). Conclusion: Our data indicate reduced circulating VEGFR-3 levels in patients with PIH, specifically in those diagnosed with pre-eclampsia. Moreover, decreased VEGFR-3 was associated with adverse clinical outcomes in pre-eclampsia. These findings expand previous evidence of reduced VEGFR-3 expression in pre-eclampsia. Future studies should investigate whether it can be used as a predictive biomarker and/or therapeutic target for pre-eclampsia.
Keywords: adverse prenatal outcomes; gestational hypertension; pre-eclampsia; pregnancy; vascular endothelial growth factor receptor; VEGFR-3